Tax Reform for Acceleration and Inclusion Act on the Socioeconomic Status of the Employees of the Polytechnic University of the Philippines - Litonjua, Lilian M.; Roque, Ryan C.; Borja, Set A.; Mercado, Kyle T.; Vincent Percival M. Penaflor, Froilan Ferdinand (International Journal of Psychosocial Rehabilitation, 2020)
The Philippines started the implementation of Tax Reform for Acceleration and Inclusion or TRAIN Act in 2018. With this, the researchers conducted this study to identify the effects of TRAIN Act on the socioeconomic status of the employees of the Polytechnic University of the Philippines (PUP) in terms of income, wealth and deprivation. Descriptive method of research was applied. Questionnaires were distributed to 189 permanent or regular employees of PUP-Mabini Campus. The study revealed that the respondents somewhat agreed with the effects of TRAIN Act in terms of all the aspects. Researchers recommend that Polytechnic University of the Philippines may conduct a seminar regarding TRAIN Act to their employees to educate them and learn about the subsidies available. Also, employees may inquire about the Unconditional Cash Transfer (UCT) which is a subsidy to lessen the impact of the increase in fuel excise tax. Employees may apply for health care card to avail better health services when needed. They should pursue continuing or graduate studies for them to have a higher position or higher salary grade. They could also borrow money from the cooperative in PUP to start their own business as another source of income.